Frota de distribuição: dimensionamento e análise de viabilidade operacional - Resende, Arnaldo Rodrigues de (2014)
Urban distribution of goods requires greater training companies in order to provide better quality and faster services in accessible prices. Therefore, proper sizing of the fleet of vehicles and reducing operational costs are essential in order to obtain efficacy and reach client satisfaction. Goods distribution can be done by own or outsourced vehicles. In both types of operational options there are favorable and unfavorable points. It is up to managers to analyze these points and to identify which situation is most advantageous for the business, ensuring productivity with quality and compatible costs. This work was developed from design vehicles through simulation in TransCAD, using a delivery database from a wholesaler in Uberlândia (MG). After sizing the fleet, operational calculations considering itself and outsourced fleets whose results showed that, compared to operational costs, it is advantageous to use the outsourced one. However, other factors must be analyzed, such as legal aspects of outsourcing activity close image of the company for costumers and service level. This work provided an insight into the complexity of distribution operation of goods towards obtain compatible market costs at the same time, to face the costumer´s satisfaction. For this purpose, managers need to be close to monitor their operations and properly utilize resources in order to generate good results for the company.